“COMPARATIVE ANALYSIS OF MALE AND FEMALE LINGUISTIC FEATURES IN THE MOVIE “MY FAIR LADY” (Contemporary Journal of Social Science Review, 2025)
This study analyzes the linguistic differences between male and female characters in the film My Fair Lady (1964) through a feminist linguistic lens. Drawing upon Robin Lakoff’s theory of women’s language (2004) and Dale Spender’s critique of patriarchal discourse (1998), the research examines how language functions as a marker of gender, class, and power. Focusing on the dialogues between Eliza Doolittle and Professor Henry Higgins, the study highlights how linguistic prejudice, accent modification, and social mobility intersect within a patriarchal hierarchy. Findings suggest that women’s linguistic conformity is portrayed as essential to social acceptance, revealing the ideological bias embedded in both language and culture.